Sex Differences in Dysfunctional Movements and Asymmetries in Young Normal Weight, Overweight, and Obese Children - Pat R. Vehrs; Haley Barker; Misea Nomiyama; Zachary Vehrs; Miklόs Tόth; Martina Uvacsek; Ulrike H. Mitchel; Aaron W. Johnson (MDPI AG, 2021)
This study evaluated overall performance on the functional movement screen (FMS), prevalence of asymmetries and dysfunctional movements, and the relationship between measures of adiposity and the FMS score. Methods: Ninety-four (53 boys; 41 girls) 10-12-year-old children in Hungary and Germany who were participating in daily physical education performed the FMS. The mean FMS score in girls (14.1) was significantly higher than in boys (12.9). Individual test item scores were similar, except girls scored higher on the straight-leg raise. Most children (55% of boys, 68% of girls) presented with at least one asymmetry and 72% of boys and 76% of girls had at least one dysfunctional score. Measures of adiposity were negatively correlated to performance on all test items. Underweight and normal weight children performed significantly better on the FMS than overweight and obese children. Sex differences and the high prevalence of asymmetries and dysfunctional scores should be interpreted with caution since they may be due to dynamic changes in strength, proprioception, balance, and motor control that occur as part of growth and involvement in activities. Nevertheless, the high prevalence of asymmetries and dysfunctional scores indicate that most children have movement limitations.